Which qualifications does a minister of the German Federal Government need to be reoccupied? - Katrin Scharfenkamp (Westfälische Wilhelms-Universität Münster, Centrum für Interdisziplinäre Wirtschaftsforschung (CIW), 2013)
The objective pursued by this study is to raise the question whether there exists a correlation between the reoccupation of ministers of the German Federal Government and their particular socio-demographic characteristics or human capital. Therefore, this paper depicts the decision of the German Federal Chancellor of reoccupation for all ministers between 1949 and 2012 by running several ordinal regression analyses. The results reveal that the age, the years of membership in the German Bundestag or in the party, as well as previous leaderships of German non-partisan non-profit organisations or business corporations significantly increase the probability of reoccupation. In addition, this analysis points out that the comparably prominent position of the vice chancellor also raises the chance to be reappointed. – – Untersuchungsgegenstand dieser Studie ist die Fragestellung, ob ein Zusammenhang zwischen der Wiederberufung von Ministern der deutschen Bundesregierung und ihren jeweiligen soziodemographischen Eigenschaften oder ihrem Humankapital besteht. Zu diesem Zweck bildet dieses Papier die Entscheidung des/der deutschen Bundeskanzlers/in über eine Wiederberufung für alle Minister zwischen 1949 und 2012 durch die Berechnung diverser ordinaler Regressionsanalysen ab. Die Ergebnisse zeigen, dass sowohl das Alter, die Mitgliedschaftsdauer im deutschen Bundestag oder in der Partei als auch frühere Führungspositionen in deutschen nicht-politischen Non-Profit-Organisationen oder Unternehmen signifikant die Wahrscheinlichkeit einer Wiederberufung erhöhen. Außerdem stellt diese Analyse heraus, dass die vergleichsweise prominente Position des Vizekanzlers auch die Chance, wiederberufen zu werden, signifikant erhöht.
Keywords: C81; J24; L88; M53; O52; 330